2017
DOI: 10.4328/jcam.4631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Smoking and Risk Factors Among Students at a University in Turkey

Abstract: Bu çalışmada iç Anadolu'da bulunan bir üniversitenin sağlık yüksekokulu ile Beden eğitimi ve spor yüksekokulunda okuyan öğrencilerin sigara kullanım prevalansı ve buna bağlı risk faktörlerinin tespit edilmesi amaçlanmıştır. Gereç ve Yöntem: Tanımlayıcı tipteki bu çalışmada Ekim-Aralık 2015 tarihleri arasında eğitime devam 1082 öğrenciye uygulanmıştır. Veriler, literatür taraması ile oluşturulan çoktan seçmeli anket ile yüz-yüze görüşme yöntemiyle toplanmıştır. Bulgular: Çalışmaya katılan 1082 kişiden 675 kişi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…While those with passing and notable marks represent approximately one out of every five smokers with medium dependency. The consumption of harmful substances to health is negatively related to implicit factors in the educational environment, as it is evident in some studies whether these substances may harm the academic performance of young people [ 58 , 59 ]. On the contrary, there is also research that has not found relationships between academic variables and the consumption of harmful substances [ 60 , 61 ]; this may be motivated by establishing the frequency and duration of substance consumption, understanding prolonged consumption as the one that carries negative or more disturbing consequences for health.…”
Section: Discussionmentioning
confidence: 99%
“…While those with passing and notable marks represent approximately one out of every five smokers with medium dependency. The consumption of harmful substances to health is negatively related to implicit factors in the educational environment, as it is evident in some studies whether these substances may harm the academic performance of young people [ 58 , 59 ]. On the contrary, there is also research that has not found relationships between academic variables and the consumption of harmful substances [ 60 , 61 ]; this may be motivated by establishing the frequency and duration of substance consumption, understanding prolonged consumption as the one that carries negative or more disturbing consequences for health.…”
Section: Discussionmentioning
confidence: 99%